Using HI stacking to study galaxy properties in the nearby universe (Looking for needles in the HI-stack) - Healy, Julia L (Department of Astronomy, 2017)
Neutral atomic hydrogen (Hi) is the raw fuel from which the star-forming molecular gas forms and is therefore an important tracer of galaxy evolution. Due to the intrinsic faintness of the Hi emission line (observed at rest at 21 cm), galaxies beyond a few hundred megaparsecs are difficult to observe directly with current radio telescopes. However, in the next year, MeerKAT and other SKA pathfinder telescopes will begin operating and enable deeper, large surveys (e.g. LADUMA) of neutral gas in galaxies. Hi Stacking is an observational technique that will be highly exploited to learn about the Hi content of galaxies that are not directly detected. Stacking involves combining the Hi spectra of all the galaxies in a distant sample, thereby generating a high signal-to-noise measure of their average Hi content. This work presents a new Python-based package capable of stacking Hi galaxy spectra. This package will be used to stack the Hi spectra of high-redshift galaxies observed with the MeerKAT telescope. In this work the package is applied to a sample of galaxies observed as part of the Nançay Interstellar Baryon Legacy Extragalactic Survey (NIBLES, van Driel et al. (2016)) to learn more about the gas properties of galaxies in the local universe. Using the stacking technique, we are able to recover the average Hi mass of different galaxy populations for which there was no Hi directly detected. In order to obtain the average gas properties that best represent the overall galaxy populations, we also stack both the Hi detected and non-detected spectra from the NIBLES survey. We find that our gas fraction vs. stellar mass distribution results agree well with previous stacking experiments (Brown et al., 2015; Catinella et al., 2010; Fabello et al., 2011a) and the NIBLES sample enables us to probe an order of magnitude lower in stellar mass. We find a dependence on the underlying stellar mass distribution for our gas fraction vs. NUV - r colour, especially when comparing to Brown et al. (2015) and Fabello et al. (2011a).